Does corporate governance mechanism deter earnings management and enhance readability of annual reports? - Dong Zheng; Rajib Ali; Zhao Feifei; Muhammad Shaique (PLoS ONE)
This study aims to know the impact of earnings management (accrual, real and total) and corporate governance mechanisms on the readability of annual reports. Additionally, the study also seeks to know the moderating impact of corporate governance mechanisms between earnings management (accruals, real and total) and readability of annual reports. The sample of the study consists 250 listed firms of Pakistan Stock Exchange (PSX) for the period of 2014-2022. The hypotheses are tested using System GMM technique. The results of the study suggest that earnings management (accruals, real and total) has negative and significant impact on readability of annual reports. However, all four corporate governance mechanics have a significantly positive impact on readability of annual reports. Additionally, corporate governance mechanics significantly moderates the relationship between earnings management (accruals, real and total) and the readability of annual reports. This study has practical implications for regulators, investors, and firms. The findings of the study may suggest to the Security Exchange Commission Pakistan that authorities improve readability by requiring companies to use clear, understandable language and include appropriate information in annual reports. Firms listed on PSX need to produce more readable annual reports to make information more concise and clear, using simple and short sentences, and familiar words.